2008
DOI: 10.1002/maco.200804104
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of corrosion inhibition of benzotriazole to copper in 3.5% NaCl

Abstract: The kinetics of interaction of benzotriazole (BTAH) with the surface of copper were studied using an electrochemical quartz crystal microbalance (EQMB) and electrochemical impedance spectroscopy (EIS). Upon injecting BTAH into the electrolyte, three regions appear in the time response of the microbalance. Region I (at short time scale of few minutes) exhibits rapid linear growth of mass with time. This is attributed to the formation of a Cu(I)BTA film that is several hundred layers thick. Region II reveals ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The electrochemical quartz crystal microbalance ͑EQCM͒ technique has been employed to study the kinetics of forming multilayers of BTA over time scales of the order of hours. 40,41 Unfortunately, the resolvable time scale of the EQCM, about 0.1 s, 42 limits the usefulness of this technique for studying the millisecond time scale. Hence, we employed a theoretical approach using our experimental chronoamperometric data to determine the rates of dissolution of copper from bare copper sites and from the sites that are occupied by BTA and then used these data to calculate the kinetics of adsorption of BTA onto copper.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…The electrochemical quartz crystal microbalance ͑EQCM͒ technique has been employed to study the kinetics of forming multilayers of BTA over time scales of the order of hours. 40,41 Unfortunately, the resolvable time scale of the EQCM, about 0.1 s, 42 limits the usefulness of this technique for studying the millisecond time scale. Hence, we employed a theoretical approach using our experimental chronoamperometric data to determine the rates of dissolution of copper from bare copper sites and from the sites that are occupied by BTA and then used these data to calculate the kinetics of adsorption of BTA onto copper.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Copper corrosion inhibition is the system that is studied most often [37][38][39][40][41][42]. G. Trabanelli et al [37], who studied the corrosion inhibition of copper by various heterocyclic compounds (BTA, 2,4-dimercapto-pyrimidine, 5-mercapto-1-phenyltetrazole, 1H-1,2,3-triazolo [4,5-b]pyridine) in 0.1 M NaCl concluded that "EQCM technique has a valuable part to play in the interpretation of corrosion and corrosion inhibition mechanisms".…”
Section: Adsorption Of Organic Cis On Metals From Neutral Aqueous Solmentioning
confidence: 99%
“…[54 " 56] It has been recently reported to be an effective corrosion inhibitor for iron [57 ' 58] and aluminum alloys.…”
Section: 5 Corrosion Preventionmentioning
confidence: 99%